Diallel analysis of maize in inbred lines (Zea mays) for resistance to striga (Striga hermonthica) - Haruna, Alidu (University of Cape Coast, 2008)
Striga hermonthica (Del.) Benth. infest millions of hectares of land under cereals in sub-Saharan Africa, threatening food security. One of the major crops threatened is maize (Zea mays L.), a staple food for many Ghanaians. The objectives of this study were to investigate the combining ability and heritability of Striga-resistant maize inbred lines for the selection of superior lines for hybridization. A diaHel cross involving ten (10) maize inbred lines was made to produce forty-five (45) Fl single crosses excluding reciprocals. All 45 Fl 's with their parents were evaluated under artificially infested Striga fields at the Savanna Agricultural Research Institute (SARI) trial farms at Nyankpala using the randomized complete block design. The genotype means were partitioned into general combining ability (gca) and specific combining ability (sca) effects according to Griffing method 2 model 2 diallel. The study found gca and sca effects to be significant (p < 0.01) for grain yield, days to flowering, plant height and Striga emergence count (STEC). Both additive and non-additive gene actions were thus responsible for these traits. The ratios of gca to sea components were relatively low, from 0.09 (STEC) to 0.46 (days to 50% silking), indicating that sca was important in predicting the F I hybrid performance. Heritability values for grain yield, days to flowering, plant height and STEC ranged from 0.72 for STEC to 0.98 for plant height, indicating that these traits can easily be transferred from the inbred lines to the single-cross hybrids. Inbred lines TZISTR 101, TZISTR 108 and TZISTR 102 were found to have good combining abilities for Striga resistance and may be exploited for single - cross hybrid development.
xv,142p.:ill.
Keywords: land; Striga